The Potential for Integrating Pencak Silat Into Ethnophysics Education - Putri Rusmila; Nadi Suprapto; Suliyanah Suliyanah; Hasan Nuurul Hidaayatullaah; Adrian Bagas Damarsha; Azar Zakaria; Meydiana Arnyan Putri (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to describe the trends, contributions, opportunities, and developments in ethnoscience research on pencak silat. The method used in this study is bibliometric analysis using Biblioshiny. Data was collected through the Scopus database by searching “TITLE-ABS-KEY (Pencak Silat OR Local Wisdom AND Physics Learning OR Ethnoscience),”. The data obtained used screening from 2015 to 2025 and English, resulting in 528 documents. The results show that ethnoscience research has increased since 2015. This indicates that ethnoscience research is trending. The contributors to ethnoscience research are Kuswanto H and Suprapto N, while the contributing affiliations are Universitas Negeri Yogyakarta and Universitas Negeri Surabaya. Opportunities for conducting ethnoscience research are greater, as evidenced by network visualization and average citations. Opportunities for international publication of ethnoscience can be through conferences, namely the Journal of Physics: Conference Series have 86 documents, and journals, namely the Jurnal Pendidikan IPA Indonesia have 36 documents. The development of ethnoscience research has reached the stage of learning media and the context of physics learning. The results obtained can be concluded that ethnoscience research is still relevant to be conducted. If future researchers wish to add pencak silat to the context, this can be done as an opportunity for research innovation. The addition of pencak silat to the context needs to be combined with physics learning and learning media so that it becomes an opportunity for innovation in future research. This study hopes to contribute to providing a context for physics learning and cultural preservation through learning.